Genocide and resistance Nr. 11(1) - Jaseliūnas, Egidijus; Banionis, Juozas; Zizas, Rimantas; Starkauskas, Juozas; Brandišauskas, Valentinas; Streikus, Arūnas; Tatarūnas, Linas; Stanionytė-Zujienė, Gražina; Zizas, Rimantas (Genocidas ir rezistencija, 2002)
Full Issue (paper copy scan)